Interculturalism and Responsive Reflexivity in a Settler Colonial Context - Kearney, Amanda (Religions, 2019)
This article explores interculturalism in Australia, a nation marked by the impact of coloniality and deep colonising. Fostering interculturalism-as a form of empathic understanding and being in good relations with difference-across Indigenous and non-Indigenous lived experiences has proven difficult in Australia. This paper offers a scoping of existing discourse on interculturalism, asking firstly, 'what is interculturalism', that is, what is beyond the rhetoric and policy speak? The second commitment is to examine the pressures that stymy the articulation of interculturalism as a broad-based project, and lastly the article strives to highlight possibilities for interculturalism through consideration of empathic understandings of sustainable futures and land security in Australia. Legislative land rights and land activism arranged around solidarity movements for sustainable futures are taken up as the two sites of analysis. In the first instance, a case is made for legislative land rights as a form of coloniality that maintains the centrality of state power, and in the second, land activism, as expressed in the campaigns of Seed, Australia's first Indigenous youth-led climate network and the Australian Youth Climate Coalition, are identified as sites for plurality and as staging grounds for intercultural praxis.